"THE EMPEROR`S NEW MIND - CONCERNING COMPUTERS, MINDS AND THE LAWS OF PHYYSICS" - PENROSE ROGER (VINTAGE, 1990)
PHYSICS/ MIND
Keywords: "THE EMPEROR`S NEW MIND - CONCERNING COMPUTERS, MINDS AND THE LAWS OF PHYYSICS"